Keynote Remarks by World Bank Group President David Malpass to the European Union-African Union Summit on Peace, Security and Governance - Malpass, David (World Bank, Washington, DC, 2022)
These keynote remarks were delivered by World Bank Group President David Malpass to the European Union-African Union Summit on Peace, Security and Governance on February 17, 2022. He spoke about the global misallocation of capital leaves developing countries with inadequate capital flows and unable to sufficiently respond to the multitude of challenges they face. He mentioned that the World Bank Group has significantly increased their support for fragile states over the last five years, providing 15.8 billion in FY21 for over thirty fragile and conflict-affected countries, many of them in Africa. He was gravely concerned by the rapid escalation in conflicts in countries such as Burkina Faso and Ethiopia. He said that without good governance, Africa will continue to face underinvestment, insufficient access to electricity and clean water, and regulatory barriers. He highlighted on their operations working toward better outcomes in terms of reduced poverty and higher incomes which means governance that promotes trade facilitation, builds accountability mechanisms, enhances systems for service delivery, and fosters citizen engagement. He declared that the Recovery and Peacebuilding Assessment between the EU, UN, and the World Bank helps governments identify their priority needs for recovery, reconstruction, and peacebuilding. He also works with the UN Peacekeeping Missions in Democratic Republic of Congo, Mali, and the Central African Republic, where they have been able to provide rapid support once insecure areas are stabilized. He concluded with noting that by 2030, two-thirds of the world’s extremely poor people could be living in fragile countries, and together with their development partners, they must continue to ramp up our efforts to support the world’s poorest and most fragile states in becoming more resilient, peaceful, just, and economically robust.